1993
DOI: 10.2134/agronj1993.00021962008500030017x
|View full text |Cite
|
Sign up to set email alerts
|

Crop Performance Trials under Irrigated and Dryland Conditions

Abstract: Corn (Zea mays L.) and soybean [Glycine nuJX (L.) Men·.] perfonnance trials are sometimes conducted under both irrigated und dryland conditions in the southeastern USA. It is not known whether irrigated trials are better trials statistically or if irrigation causes l"l~lative rank changes in hybrid or cultivar perfonnance. To answer these questions, corn data were examined from four different environmemts and three maturity groups, and soybean data were examined from five different environments and three ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, until the regression values approach 13 = 2.0, the probability of CV values less than some desired level increases with the mean, suggesting that those who conduct performance trials would be better off conducting their trials to achieve maximum yields. For example, Bowman et al (1993) showed that irrigation per se did not decrease error variances inz ' creaseR values, or change entry F-tests; CVs were not used for comparison in that study, but were lower in the irrigated trials than the dryland trials (8.5 vs. 14.2, respectively, in corn, 10.7 vs. 14.0, respectively, in soybean).…”
Section: The Relationship For Several Cropsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, until the regression values approach 13 = 2.0, the probability of CV values less than some desired level increases with the mean, suggesting that those who conduct performance trials would be better off conducting their trials to achieve maximum yields. For example, Bowman et al (1993) showed that irrigation per se did not decrease error variances inz ' creaseR values, or change entry F-tests; CVs were not used for comparison in that study, but were lower in the irrigated trials than the dryland trials (8.5 vs. 14.2, respectively, in corn, 10.7 vs. 14.0, respectively, in soybean).…”
Section: The Relationship For Several Cropsmentioning
confidence: 90%
“…Other measures of precision or relative variation include Gini's coefficient of concentration (Kendall and Stuart, 1977), error mean square (EMS), and coefficient of determination (R 2 ) (Bowman et al, 1993;Askew et al, 1994). As a measure of precision, EMS is valid only for comparison of similar trials measured in the same units and thus would not be a useful statistic to report in cultivar performance data, but would be useful to the researcher in determining the validity of a trial (Bowman and Rawlings, 1995).…”
mentioning
confidence: 99%